Influence of rooting media, number of nodes and seedling growing methods on rooting, seedling establishment and early growth of Chaya (Cnidoscolus aconitifolius McVaugh) stem cuttings at Dire Dawa, Eastern Ethiopia - Chala Kitila; Wassu Mohammed; Kebede Woldetsadik (Archives of Anatomy and Physiology - Peertechz Publications, 2022)
Establishment of seedling growing method(s) is priority activity to the distribution of newly introduced vegetable crops. Chaya is proposed as candidate vegetable crop to distribute in eastern Ethiopia. However, recommendation is lacking for rooting media and type of cutting to produce seedlings. Therefore, this study was conducted to assess effect of rooting media and number of nodes on rooting, seedling establishment and early growth of chaya at Dire Dawa from February 2018 to July 2018. Three level of rooting media (top soil only, 3:2:1 top soil: farmyard manure: sand, 3:1 top soil: farmyard manure), three levels of node number (2, 3, 4) and two seedling growing methods (seedbed/bare root and polyethylene bag) in factorial combinations were evaluated in completely randomized and randomized complete block designs with three replications for nursery and field experiments, respectively. Seedling growing methods significantly influenced all traits, rooting media, number of nodes and interaction of the main factors had significant effect on percentage of root initiated cuttings. Fresh and dry weight of leaves and roots, dry weight of leaves and root significantly influenced by interaction of the three factors. The seedlings raised on seedbed filled with 3:1 top soil: farmyard manure (91.6%) and stem cuttings with four nodes (92.7%) showed high percentage survival. Generally, either one or more of the three main factors rooting media, number of nodes and seedling growing method or one or more of the possible two and three main factors interactions significantly influenced the seedlings growth and establishment of seedlings at the field.  In conclusion, chaya seedlings from cutting responded well to type of rooting media containing top soil: farmyard manure: sand, cutting length with three and four nodes and growing method (seedbed). Therefore, in the study area it could be advised to use combined mixtures of 3:2:1 top soil: farmyard manure: sand and stem cutting with four nodes grown on nursery bed and field establishment.